PENINGKATAN MOTIVASI DAN HASIL BELAJAR FISIKA MELALUI PEMBELAJARAN BERORIENTASI PENDEKATAN INKUIRI DI KELAS XI IPA-1 SMAN 1 BATANG GASAN - Aspar, Aspar (Sainstek : Jurnal Sains dan Teknologi, 2020)
Teacher-centered learning in Physics subject produces passive students because teachers dominate learning while students tend to listen, take notes, and do assignments. This condition does not provide space for students to be actively and creatively involved during learning which in turn decreases students' motivation and learning outcomes This condition can be improved through inquiry approach. The research aimed to increase motivation and learning outcomes in Physics through inquiry-based learning. The study employed Classroom Action Research (CAR) method in class XI IPA-1 SMAN 1 Batang Gasan in 2018/2019 Academic Year. This study consisted of 2 cycles in which each cycle consisted of planning, action, observation and reflection. Students? learning motivation data were collected using questionnaire sheets and their learning outcomes were collected through test. The results showed that inquiry-based learning increased student motivation from 68% in the first cycle to 100% in the second cycle and classical mastery of learning from 50% in cycle I to 96.4% in cycle II. It was concluded that inquiry-based learning approaches improve student motivation and learning outcomes in physics.